ANALYSIS OF THE SPATIAL DISTRIBUTION AND SOCIOECONOMIC IMPORTANCE OF INDIGENOUS TREE SPECIES IN GARUN MALAM LOCAL GOVERNMENT AREA, KANO STATE - Chubado, Abubakar Aminu; Mohammed, Salisu; Idris, Halima Abdulkadir (FUDMA Journal of Earth and Environmental Sciences, 2025)
The study analysed the spatial distribution and socioeconomic importance of indigenous tree species in the Garun Malam Local Government Area of Kano State, Nigeria. A physical survey was conducted to inventory indigenous tree species, and GPS was used to obtain geographic coordinates. A social survey method, including questionnaire administration and Focus Group Discussion (FGD), was employed to gather in-depth information on the socio-economic importance of indigenous trees in the study area. A total of 200 questionnaires were administered in ten (10) wards purposively selected. For the spatial distribution, the geographic coordinates were imported into ArcGIS to produce a map. Information on socio-economic importance was obtained through the administration of questionnaires and a Focus Group Discussion (FGD) with 18 elders in the community. The results of the findings showed that approximately 80% of the indigenous trees were found in open spaces that were not under cultivation. The study found that almost all the indigenous tree species have different uses. Additionally, more than 70% of the trees were used for food, medicine, and shelter, allowing people to engage in various trading activities involving the valuable parts of the tree. The study recommends that further research be conducted to explore additional potential uses of trees and that the indiscriminate felling of trees be discouraged.